Efficient CH3NH3PbI3 Perovskite Solar Cells Based on Graphdiyne (GD)‐Modified P3HT Hole‐Transporting Material. Issue 8 (15th January 2015) - Xiao, Junyan; Shi, Jiangjian; Liu, Huibiao; Xu, Yuzhuan; Lv, Songtao; Luo, Yanhong; Li, Dongmei; Meng, Qingbo; Li, Yuliang
<x xml:space="preserve">Abstract</x> Novel large π‐conjugated carbon material, graphdiyne (GD), as a dopant to poly(3‐hexylthiophene) (P3HT) hole‐transporting material (HTM) layer, is introduced into perovskite solar cells for the first time. Raman spectroscopy and ultraviolet photoelectron spectroscopy measurements reveal that relatively strong π–π stacking interaction occurs between GD particles and P3HT (so‐called P3HT/GD composite HTM), favorable for the hole transportation and improvement of the cell performance. On the other hand, some GD aggregates exhibit a scattering nature, and thus help to increase the light absorption of the perovskite solar cells in the long wavelength range. As high as 14.58% light‐to‐electricity conversion efficiency is achieved, superior to the pristine P3HT‐based devices. Additionally, the devices exhibit good stability and reproducibility. Time‐resolved photoluminescence decay measurements reveal that the P3HT/GD HTM can accelerate the hole extraction compared with pristine P3HT.